2017
DOI: 10.1039/c7ta06067j
|View full text |Cite
|
Sign up to set email alerts
|

Lithium ion conductivity in Li2S–P2S5 glasses – building units and local structure evolution during the crystallization of superionic conductors Li3PS4, Li7P3S11 and Li4P2S7

Abstract: The local structure phase diagram of (Li2S)x(P2S5)100−x thiophosphates derived from pair distribution function crystallization experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
320
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(361 citation statements)
references
References 61 publications
39
320
2
Order By: Relevance
“…[ 36 ] The Raman spectra (Figure S6, Supporting Information) showed ortho ‐thiophosphate species (PS 4 3− ) as the dominant species at 421 ± 1 cm −1 , known to be responsible for the high ionic conductivity in Li thiophosphate glasses. [ 37 ] In addition, hypo ‐thiophosphate species (P 2 S 6 4− ) at around 380 cm −1 were detected, in agreement with Dietrich et al for this composition. [ 37 ] The intensity of both signals were independent from the densification conditions, therefore, the concentration of PS 4 3− and P 2 S 6 4− are believed to be the same among all samples.…”
Section: Resultssupporting
confidence: 88%
“…[ 36 ] The Raman spectra (Figure S6, Supporting Information) showed ortho ‐thiophosphate species (PS 4 3− ) as the dominant species at 421 ± 1 cm −1 , known to be responsible for the high ionic conductivity in Li thiophosphate glasses. [ 37 ] In addition, hypo ‐thiophosphate species (P 2 S 6 4− ) at around 380 cm −1 were detected, in agreement with Dietrich et al for this composition. [ 37 ] The intensity of both signals were independent from the densification conditions, therefore, the concentration of PS 4 3− and P 2 S 6 4− are believed to be the same among all samples.…”
Section: Resultssupporting
confidence: 88%
“…It is mainly constructed by the unit PS43. However, by carefully checking the Raman spectrum of the intermediate in Figure , it is revealed that a large amount of normalP2normalS74 exists, which typically appears in the Li 2 S‐P 2 S 5 system with Li 2 S content <70 mol% . Therefore, an amorphous phase with low Li 2 S content should also exist in the intermediate in our study, and it will react with the thio‐LISICON III analogous phase to form Li 7 P 3 S 11 .…”
Section: Resultsmentioning
confidence: 73%
“…As for the samples prepared in ACN, the major Raman signal around 400 cm −1 is composed of three bands. In the 230°C‐heat‐treated sample, the three bands locating at 392 cm −1 , 406 cm −1 , and 423 cm −1 can be assigned to hypo‐thiodiphosphate (normalP2normalS64), pyro‐thiophosphate (normalP2normalS74) and ortho‐thiophosphate (PS43), respectively . These bands shift to high wave number in the precursor obtained after 180°C drying, especially the band attributed to PS43, which shifts evidently from 423 cm −1 to 433 cm −1 due to the coordination of ACN molecules.…”
Section: Resultsmentioning
confidence: 98%
“…Generally speaking, oxide‐based glasses exhibit rather low conductivity but better stability, whereas principally only sulfide‐based amorphous materials have achieved conductivities greater than 10 −3 S cm −1 , allowing them to be used in bulk‐type cells. Nonannealed glassy Li 2 S‐P 2 S 5 and Li 2 S‐P 2 S 5 ‐LiI exhibit conductivities of 2.8 × 10 −4 and 5.6 × 10 −4 S cm −1 , respectively, while 10 −3 S cm −1 is generally considered a benchmark for practical thick‐electrode cells . While sulfide glasses exhibit favorable mechanical properties and enable easy low‐temperature processability, they suffer from moisture stability .…”
Section: Introductionmentioning
confidence: 99%